PROFIL KONDISI FISIK ATLET KARATE SULAWESI-SELATAN MENUJU PON XIX JAWA BARAT - Mahyuddin, Reza; Awaluddin, Awaluddin (Jurnal Penjaskesrek, 2017)
The purpose of this study to determine the physical condition of the karate athlete profiles toward PON XIX West Java. This study uses survey research design. This research was conducted for 3 months from the initial test to post-test. From this research, most athletes to increase physical condition after a weight training workout for 3 months, while not increasing due to several key factors, namely the lack of discipline in training.